A comprehensive evaluation of public hospitals in Malaysia using several grey relational analysis models / Muhammad Arif Ahmad Zaki, Nur Hanis Kaha Mohd Kaharuddin and Zureen Syazira Zalman Zain - Ahmad Zaki, Muhammad Arif; Mohd Kaharuddin, Nur Hanis Kaha; Zalman Zain, Zureen Syazira (2022)
The healthcare system in Malaysia is generally divided into two types, namely public hospitals and private hospitals. Due to the increasingly expensive medical costs in private hospitals, public hospitals have become the best alternative for patients to seek the same treatment at a minimal cost. Thus, public hospitals are always dealing with a large number of patients and indirectly it becomes a challenge to provide the best services and care to patients. Hence, the medical indicators such as the number of patients: inpatients, outpatients, emergency patients, maternal patients, surgical patients, discharge patients; arrivals at specialist clinics, bed use and the average length of stay in hospital were collected for the period from 2015 to 2018. In this study, Grey Relational Analysis (GRA) models are suitable for evaluating the performance of selected public hospitals in Malaysia such as Hospital Sultanah Aminah, Hospital Melaka, Hospital Seberang Jaya and Hospital Tengku Ampuan Rahimah since it has no special requirements for sample count and data distribution. Therefore, to provide a comprehensive evaluation, Deng’s correlation degree was used to provide a ranking, while Grey absolute correlation degree and Grey relative correlation degree to analyse the main influential indicators of hospital operations management. Finally, the results show that Hospital Sultanah Aminah ranks first place followed by Hospital Tengku Ampuan Rahimah, Hospital Melaka and Hospital Seberang Jaya. In addition, the top three influencing factors were found to be arrivals at the specialist clinic, average length of stay (ALOS) and maternal patients. The combined results of the three GRA models as evaluations have provided new and comprehensive assessment techniques for hospital operations management as a reference for future improvement.